La tradición antigua del texto virgiliano: Notas acerca de algunas hipótesis recientes - Ángel Escobar (Exemplaria Classica, 2008)
The textual transmission of Virgil in antiquity is a difficult and controversial issue. Recent decades have witnessed some essential contributions, such as those by Zetzel, Timpanaro or Courtney. This paper examines some recent publications on this matter, especially Velaza, Itur (2001), in order to show the persistence of some open questions and the difficulties of a "new pattern" of explanation.